Real-Time Thermoacoustic Imaging-Guidance for Breast Tumor Resection - Huan Qin; Yongsheng Cui; Zhujun Wu; Qun Chen; Da Xing (IEEE Photonics Journal, 2020)
In situ image guidance is one of the key techniques for accurate diagnosis and treatment in clinical medicine. Conventional imaging techniques such as CT, MRI provide critical information for diagnosis and treatment planning, but are less practical due to either technical complexity or ionizing radiation-related safety. Microwave-pumped thermoacoustic imaging (MTAI) is a promising alternative to real-time bioimaging due to its deep imaging depth, high resolution and minimal biological hazards. More importantly, by mapping the distribution of microwave absorbers, this method can also provide a new perspective for noninvasively observing the anatomy and functional structure of the target. In this work, we introduce a concept of in situ MTAI guidance by combining MTAI and an accurate spatial definition of invasive apparatus used in potential procedures. By mounting tiny MTAI beacons on the apparatus, it is possible to accurately reconstruct the relative position of the device to the target tissue for either real time visual guidance or as the foundation for potential automated procedures. The image quality including its applicable depth and resolution, the accuracy of the device localization is analyzed and tested with simulated breast tumor to demonstrate the capacity of the proposed technique. With refined adaptation for potential applications, this technique may provide a novel approach for a broad range of medical and biological applications.